Foreign Body Reaction Associated With Artificial LARS Ligaments: A Retrieval Study. Issue 12 (1st December 2018) - Sinagra, Zachary Paul; Kop, Alan; Pabbruwe, Moreica; Parry, Jeremy; Clark, Gavin
Background: Artificial ligaments have been developed and used in the treatment of ligamentous injuries since the 1970s. The early generation of artificial ligaments showed promising short-term results but resulted in high rates of rupture and inflammatory reaction in the surrounding tissues. Purpose: To determine whether the use of Ligament Augmentation and Reconstruction System (LARS) ligaments is associated with the development of intra-articular foreign body reaction. Study Design: Case series; Level of evidence, 4. Methods: LARS ligaments were explanted from 15 patients under 6 consultant orthopaedic surgeons at 8 surgical centers. Of these, 14 explanted samples were sent for macroscopic and histological analysis, with the 1 remaining sample sent for scanning electron microscopy, to assess for inflammatory change as well as the degree of fibrous tissue ingrowth. Results: We observed a foreign body reaction in 10 of 14 explanted LARS ligaments. Seven samples demonstrated fibrous tissue ingrowth, with 5 producing only focal or incomplete ingrowth. The 2 samples with extensive fibrous coverage were completely free of any foreign body reaction, while all 5 remaining samples with only focal or partial fibrous ingrowth were associated with at least some degree of harmful immune response. Conclusion: The LARS ligament is still associated with a clinically significant degree of foreign body reaction despite the LARS Company's efforts to reduce complications through improved design. The development and completion of fibrous tissue ingrowth may work to reduce the occurrence of a foreign body reaction.